On the Liouville 2D dilaton gravity models with sinh-Gordon matter - Valeri P. Frolov; Andrei Zelnikov (Journal of High Energy Physics, 2018)
Abstract We study 1 + 1 dimensional dilaton gravity models which take into account backreaction of the sinh-Gordon matter field. We found a wide class of exact solutions which generalizes black hole solutions of the Jackiw-Teitelboim gravity model and its hyperbolic deformation.